Exploring differences between organisational cultures in a company undergoing change - Bowa, Mabvuto (Rhodes University, Faculty of Humanities, Department of Psychology, 2003)
Change is a common phenomena in business organisations today. The turbulent environment is exerting a significant influence on organisations to make continuous changes in their internal environment in an attempt to improve performance and achieve competitiveness in the marketplace. The human factors which confront organisations undergoing change have not been thoroughly investigated in Sub-Saharan Africa. The present study aimed at investigating human issues affecting the performance ofan organisation located in an Afiican country. Data was collected using semi-structured interviews and focus groups. Twenty interviews were conducted with employees randomly selected from all the levels of the company, namely attendant, operator, supervisory, middle and top management. Five focus groups were carried out with employees from different employee categories. Both sets of data were analysed using grounded theory. The findings showed that there were several problems in the company including insecurity, lack of opportunities for employee development, autocratic management style, lack of participation in decision making, substandard performance, ineffective human resources systems and lack of adaptation to technology. It was suggested that the problems resulted from the clash between organisational cultures in the company. At one level, there was a clash between the local workers' socialist organisational culture and the expatriates' capitalistic organisational culture. At a more deeper level, the clash appeared to be between the local employees' collectivistic sociocultural values and the expatriates' individualistic value system. These findings have significant implications for managing change in organisations with diverse cultures.
Keywords: Organizational change -- Africa; Corporate culture -- Africa; Management -- Africa; Organizational behavior -- Africa